Bupati or Regent? Martanagara of Bandung 1893–1918 - Pratama, Raistiwar (Lembaran Sejarah, 2024)
This paper aims to unfold the dual roles of being local rulers in Indonesia during early twentieth century by reading closely various collections of colonial archives kept at the National Archives of the Netherlands, contemporary newspapers online provided by Delpher and onsite by the Library of Leiden University, and the autobiography of the man himself written in his own mother tongue, Sundanese. It is a rather common view that the Dutch government had been applied indirect ruling policy, but creative responds of the local rulers towards the one-sided policy were rarely considered to be important. By using concept of “middleman” the dual roles of Martanagara of Bandung might shed a light to understand some local rulers’ perspective. His roles both as regent and bupati put himself between two confusing and different worlds but he managed to do so. Ahead of Max Weber’s three ideal types, Martanagara succeeded applying his own ideal types by serving his foreign rulers and at the same time towards his local inhabitants.